In-vitro Evaluation of Urea and Zinc Sulphate with Comparison of Polluted Water on the Growth of Chilli under Drip Irrigation system - Kiran, Ayesha; Dr. Abdul Hannan; Arooj Abbas; Muhammad Shafqat Shaukat; M. Ahsan ul Haq (Journal of Basic and Emerging Sciences, 2025)
Application of micronutrients is increasing day by day because they promote growth quickly and ultimately increases the yield of field crop, while polluted water used for irrigating crop has negative effect on growth and development of crop. Drip irrigation saves water and nutrients and also minimizes the disease risk. An experiment was conducted to investigate the different supplements (Zinc Sulphate, Urea and Polluted Urea) through drip irrigation on the growth of chilli. Two varieties of chilli (I and II) were used in this study with four replications. During current study number of leaves and height of seedling were measured regularly and data were analyzed. Zinc Sulphate (ZnSO4), Urea (CO(NH2)2) and polluted water were compared with control group. Chilies irrigated with zinc sulphate show less growth than control because large quantity of zinc sulphate was applied. Polluted water has negative effect on growth of crop that’s why chilli showed minimum growth. While maximum growth were recorded after the application of urea that was 8.82% more than control in variety I and in variety II growth were 5.78% more than control group.